Measuring Public Digital Awareness and Perception of The Transfer of Management of Soekarno-Hatta International Airport Railway Through a Digital Change Communication Strategy - Atikah; Rizal, Sofyan; Fadillah, Sobari; Sunaryanto (International Journal of Science and Society, 2025)
This study examined the influence of awareness and perception on digital change communication and its impact on the transfer of management of the Soekarno-Hatta Airport Rail Link. The service, initially managed by PT Railink in 2018, was officially transferred to PT Kereta Commuter Indonesia (KCI) in 2023 as part of efforts to improve public transportation integration in the Greater Jakarta area. A quantitative approach with inferential statistical analysis was employed to test the relationships among the variables. The findings revealed that awareness did not significantly affect digital change communication, indicating that the level of awareness alone was not sufficient to enhance communication effectiveness. In contrast, perception significantly influenced digital change communication, showing that positive public perceptions could strengthen digital communication efforts. Furthermore, digital change communication had a significant effect on the transfer of management, emphasizing its crucial role in facilitating organizational transitions. The conclusion highlighted that effective digital communication strategies were essential in ensuring smooth management transitions in public transportation services.